Optimasi Laporan Keuangan Pondok Pesantren Melalui Pengetahuan Akuntansi, Pemanfaatan Teknologi Informasi dan SDM - Andriani, Ai Sindi; Pekerti, Retno Dyah (Jurusan Akuntansi Fakultas Ekonomi Universitas Siliwangi, 2024)
This study aims to examine the influence of accounting knowledge, the utilization of information technology, and human resources in the field of accounting on the quality of financial reports at Islamic boarding schools (pondok pesantren) in Tasikmalaya Regency. The research method used is a survey method with a descriptive quantitative approach. Testing was conducted using the structural equation model (SEM) with SmartPLS software. The sample for Islamic boarding schools was determined using Slovin's formula, resulting in a total of 93 boarding schools, while the respondents' sample was selected through purposive sampling. Tasikmalaya was chosen as the research location due to the high number of boarding schools, totaling 1,344. The results of the study show that: (1) Accounting Knowledge has a positive effect on the Quality of Financial Reports, (2) Utilization of Information Technology positively impacts the Quality of Financial Reports, and (3) Human Resources in the Accounting Field positively influence the Quality of Financial Reports. These findings can serve as a benchmark for Islamic boarding schools in selecting and placing financial managers aligned with the required expertise and provide practical guidance to improve the quality of financial reporting as part of boarding school management strategies.